Rectangular Microstrip Patch Antenna With Different Location Of Minkowski Island Split Ring Resonator (MI-SRR) Structure - Hassan, Nornikman; Noor Azizi, Muhammad Syafiq; Ahmad, Badrul Hisham; Abd Aziz, Mohamad Zoinol Abidin; Abu Bakar, Hamizan; Ramli, Mohamad Hafize; Othman, Mohd Azlishah; Sulaiman, Hamzah Asyrani (Penerbit Universiti, UTeM, 2017)
-